PROSES MANUFAKTUR SHEET PRESS MACHINE DAUR ULANG SAMPAH PLASTIK SKALA MIKRO - Parar Tria Dipa Galatian, (2023)
Plastic is one of the products of human invention that is widely used for various needs. However, the population continues to increase every year resulting in plastic that is no longer used becoming a pile of waste and is very difficult to decompose. Plastic is classified as a recycle product because it can be managed by recycling as an effort in handling plastic waste so that it becomes a useful product. In order to implement this idea, a micro-scale sheet press machine with dimensions of 500 x 400 x 650 mm has been designed. The raw material required is 0.5 kg of HDPE plastic shreds for one hour. The workflow of this machine starts from the preparation of raw materials on the casting mall which will be pressed with hydraulic jacks, heating with temperatures up to 130 ℃, and the cooling process. After conducting functional test on the sheet press machine, the resulting product is a plate with dimensions of 30 x 27 cm and 3 mm thickness. The total time required for pressing from the beginning to the end is 60 minutes. The product outcome of this sheet press machine can be made into various products with advanced fabrication processes.